Clostridioides (Clostridium) difficile Pacemaker Infection. (14th October 2020) - Berkefeld, Anna; Berger, Fabian K; Gärtner, Barbara C; Wantia, Nina; Prinzing, Anatol; Laugwitz, Karl-Ludwig; Busch, Dirk H; Rothe, Kathrin
Abstract: Clostridioides difficile is the leading cause of antibiotic-associated nosocomial diarrhea, but extra-intestinal manifestations are rare. We describe the first documented case of bacteraemia with pacemaker pocket and lead infection with the toxigenic C. difficile ribotype 014 with a lack of abdominal symptoms. The patient underwent pacemaker extraction and treatment with intravenous and oral vancomycin. Genotyping and molecular subtyping revealed clonality between pacemaker and intestinal isolates. This case illustrates the risk of intravascular device infections due to C. difficile . Even asymptomatic C. difficile colonization might pose a risk for prosthetic material infection. Graphical Abstract: